The challenge of making EVs just affordable enough: Assessing the impact of subsidies on equity and emission reduction in Ireland - Caulfield, Brian (My University, 2025)
Governments support the switch to electric vehicles (EVs) through subsidies and other incentives, as this is expected to help meet climate targets. This research examines the affordability of EVs for Irish households, focusing on equity implications and the impact of affordability on achieving decarbonisation goals. Affordability is estimated for eight scenarios, considering both current and reduced EV prices, and assessed across Ireland. The research finds that flat-rate subsidies do not adequately support lower-income households, impede EV adoption, and could jeopardise the achievement of emission reduction targets. Need-based subsidies would ensure more inclusive EV uptake. If current prices are considered, the target for the number of EVs on the road by 2030 can be met only with the purchase of small-sized EVs. This suggests that achieving EV targets is unlikely without promoting smaller vehicles. The current €3500 EV grant may be insufficient for many households without extended loan terms. Therefore, differentiated subsidies based on income and household size are recommended to increase EV adoption. Households in remote rural areas, where forced car ownership is high, require higher subsidies. In contrast, urban areas could receive lower subsidies to promote the use of more sustainable transport modes, such as cycling, shared mobility, and public transport.
PUBLISHED
Keywords: Household income; Affordability; Equity; Policy incentives; Subsidies; Electric vehicles; Climate change; Decarbonisation; Smart & Sustainable Planet; Environmental aspects of transportation; Transport